Impact of personal and social resources on parenting stress in mothers of children with autism spectrum disorder. (February 2017) - Zaidman-Zait, Anat; Mirenda, Pat; Duku, Eric; Vaillancourt, Tracy; Smith, Isabel M; Szatmari, Peter; Bryson, Susan; Fombonne, Eric; Volden, Joanne; Waddell, Charlotte; Zwaigenbaum, Lonnie; Georgiades, Stelios; et al.
This study examined the longitudinal associations between child behavior problems, coping strategies, social resources, and parenting stress in mothers of young children with autism spectrum disorder. Participants were 283 mothers who completed self- and child-report measures at the time of diagnosis and 2 years later. Hierarchical multiple regression was conducted to predict overall parenting stress. At diagnosis, the final model indicated that high levels of social support and mothers' use of active engaged coping strategies were associated with lower levels of parenting stress. Conversely, high levels of child externalizing behavior problems, family dysfunction, and mothers' use of disengaged coping strategies were associated with higher parenting stress. Two years later, high levels of parenting stress at diagnosis predicted increased parenting stress. In addition, high or increasing levels of social support predicted a decrease in parenting stress, while high or increasing levels of family dysfunction predicted increased stress. Finally, increased use of disengaged coping strategies and decreased use of active coping strategies over time predicted higher levels of parenting stress. Results are discussed in terms of their implications for the provision of targeted supports that are designed to enhance the personal and social resources available to mothers of children with autism spectrum disorder.